Proceedings of the 26th International Nuclear Physics Conference — PoS(INPC2016) 2017
DOI: 10.22323/1.281.0145
|View full text |Cite
|
Sign up to set email alerts
|

Impact Of Pairing Correlations On The Chemical Composition Of The Inner Crust Of A Neutron Star

Abstract: We investigate the impact of the role of pairing correlation on the energy per particles of Wigner-Seitz cells in the inner crust of a neutron star. In particular, we compare some common approximations done to treat pairing effects and we estimate the possible error. To reduce the computational cost of the calculations required to determine the chemical composition of the crust, we present a new numerical method based on Gaussian Emulator Process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…In Ref. [78], we have shown that the errors are typically one order of magnitude larger than the value estimated in Eq. 19 when semi-classical methods are adopted (i.e.…”
Section: E Summary Of the Sources Of Errormentioning
confidence: 62%
“…In Ref. [78], we have shown that the errors are typically one order of magnitude larger than the value estimated in Eq. 19 when semi-classical methods are adopted (i.e.…”
Section: E Summary Of the Sources Of Errormentioning
confidence: 62%
“…A further simplification is to solve the HF+BCS equations instead of the full HFB equations. Systematic calculations have recently shown that the error on the total energy amounts to a few keV per nucleon at most [59]. The Wigner-Seitz approximation allows for relatively fast numerical computations, but is unreliable in the densest region of the crust due to the appearance of spurious neutron shell effects [60,61,62].…”
Section: Application To Neutron-star Crustsmentioning
confidence: 99%
“…The neutronisation of matter leads to the production of very neutron rich nuclei. The process continues until the drip-line is reached and neutrons start dripping off forming a uniform gas [3,4,5,6,7,8,9]. This region of the star is called the inner crust.…”
Section: Introductionmentioning
confidence: 99%